PENURUNAN KADAR GLUKOSA DARAH PASIEN DM MENGGUNAKAN KOMBINASI PEBERIAN SIMPLISIA OKRA DAN MUROTTAL AL-QUR’AN - Aldi, Leo; lestari, trijati puspita; Faridah, Virgianti Nur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Blood glucose levels in diabetes mellitus patients are often difficult to control, which can lead to complications such as chronic kidney disease (CKD), hypertension, and coronary heart disease (CHD). Therefore, aside from the five pillars of diabetes mellitus management, complementary therapy such as consuming okra simplisia infusion and listening to Murottal Al-Qur’an therapy may provide additional benefits. Methods: This study employed a pre-experimental one-group pretest-posttest design. The sample consisted of 61 diabetes mellitus patients, selected from a population of 126 Chronic Diseases Management Program (Prolanis) members at Kedungpring Community Health Center, using purposive sampling. The independent variable was the combination of okra simplisia consumption and Murottal Al-Qur'an therapy, while the dependent variable was blood glucose levels. Measurements were conducted before and after the intervention using a glucose meter, and data were analyzed using the Wilcoxon Signed Rank Test. Results: The results indicate that the mean blood glucose level decreased from 234 mg/dL before the intervention to 184 mg/dL after the intervention. The Wilcoxon test showed a significant difference in blood glucose levels before and after the intervention (p=0.000, P<0.05). Conclusion: The findings suggest that okra functions as a biological agent affecting biochemical mechanisms in the body, while Murottal Al-Qur’an serves as a psychological agent helping regulate blood glucose levels.